Metabolic engineering for sustainable xylitol production from diverse carbon sources in Pichia pastoris - Xiaocong Lu; Mingxin Chang; Xiangyu Li; Wenbing Cao; Zhoukang Zhuang; Qian Wu; Tao Yu; Aiqun Yu; Hongting Tang (Microbial Cell Factories)
Abstract Xylitol, known for its health benefits, is a valuable compound in the food and pharmaceutical industries. However, conventional chemical production methods are often unsustainable for large-scale applications, prompting the need for alternative approaches. This study demonstrates a significant enhancement in xylitol production using microbial cell factories, optimized through metabolic engineering. Two synthetic pathways were combined, and the introduction of a novel NADPH-dependent xylitol dehydrogenase further boosted xylitol yields, achieving 0.14 g xylitol/g glucose—a record-high yield for microbial systems. Additionally, the use of sustainable feedstocks, such as glycerol and methanol, led to the production of 7000 mg/L xylitol with a yield of 0.35 g xylitol/g glycerol, and 250 mg/L xylitol from methanol. These results underscore the potential for eco-friendly, cost-effective xylitol production, providing a robust foundation for future industrial-scale biotechnological applications.